How teachers interact and use teacher guides in mathematics – cases from Sweden and Iceland - Ahl, Linda; Gunnarsdóttir, Guðný Helga; Koljonen, Tuula; Pálsdóttir, Guðbjörg (NOMAD Nordic Studies in Mathematics Education, 2015)
Recent research findings show that curriculum resources have a potential to support teachers’ design of lessons. The aim of this study is to investigate how Icelandic and Swedish teachers interact with and use teacher guides while planning their teaching. Five teachers in each country teaching lower grade levels (1–6) were interviewed about their utilization of teacher guides. The analytical tool used to analyse the teacher guides and the interviews focused on the different features of the guides and shed light on what the teachers were looking for in the guides and for what purpose. Our findings showed that teachers using educative teacher guides were more likely to use a wider range of lesson design considerations in contrast to teachers using traditional teacher guides.